Expanded criteria donors in deceased donor kidney transplantation – An Asian perspective - Ziting Wang; Pradeep Durai; Ho Yee Tiong (Indian Journal of Urology, 2020)
There is an increasing gulf between demand and supply for kidneys in end-stage renal failure patients worldwide, especially Asia. Renal transplantation is often the treatment of choice for long-suffering patients who have to undergo dialysis on a regular basis. The utilization of expanded criteria donors (ECDs) to address the donor pool shortage has been proven to be a legitimate solution. Metzger first described the classification of standard criteria donor and ECD in 2002. Since then, the criterion has undergone various modifications, with the key aims of optimizing organ procurement rate while minimizing discard and rejection rates. We review the methods to improve selection, characterization of risks, and surgical techniques. Although the ECD kidneys have a higher risk of impaired donor and recipient outcome than the “standard criteria” transplants, it may be justified by the improved overall survival of these patients compared to those who remained on dialysis. It is, therefore, crucial that we perform meticulous selection, along with state of the art surgical techniques to maximize the use of this scarce resource. In this article, we review the pre-procurement and post-procurement processes implemented to preserve outcomes.